Memory Potential Herb: A Review (World Journal of Current Medical and Pharmaceutical Research, 2021)
Memory is an important aspect of cognition. For its health-promoting qualities, Ayurveda is gaining popularity and attention in many areas of the globe. Dementia is a condition in which a person's mental and cognitive abilities gradually deteriorate. Dementia has been related to a number of risk factors and circumstances, including inadequate cerebral blood flow, toxin exposure, mitochondrial malfunction, and oxidative damage, and it often coexists with other neurodegenerative diseases, such as Dementia and memory loss. As a consequence, the present research focuses on the many herbal ayurvedic medicinal plants and their connection to memory functions.